Nature-based mindfulness programs using virtual reality to reduce pediatric perioperative anxiety: a narrative review - Benchimol-Elkaim, Brandon; Khoury, Bassam; Tsimicalis, Argerie (Frontiers in Pediatrics, 2024)
Over 75% of pediatric surgery patients experience preoperative anxiety, which can lead to complicated recoveries. Current interventions are less effective for children over 12 years old. New interventions, like mindfulness-based ones (MBIs), are needed to address this issue. MBIs work well for reducing mental health symptoms in youth, but they can be challenging for beginners. Virtual reality (VR) nature settings can help bridge this gap, providing an engaging 3-D practice environment that minimizes distractions and enhances presence. However, no study has investigated the combined effects of mindfulness training in natural VR settings for pediatric surgery patients, creating a significant gap for a novel intervention. This paper aims to fill that gap by presenting a narrative review exploring the potential of a nature-based mindfulness program using VR to reduce pediatric preoperative anxiety. It begins by addressing the risks of anxiety in children undergoing surgery, emphasizing its impact on physical recovery, and supporting the use of VR for anxiety reduction in hospitals. The review then delves into VR's role in nature and mindfulness, discussing theoretical concepts, clinical applications, and effectiveness. It also examines how the combination of mindfulness, nature, and VR can create an effective intervention, supported by relevant literature. Finally, it synthesizes the existing literature's limitations, findings, gaps, and contradictions, concluding with research and clinical implications.